2001
DOI: 10.1152/ajpendo.2001.281.2.e197
|View full text |Cite
|
Sign up to set email alerts
|

Timing of amino acid-carbohydrate ingestion alters anabolic response of muscle to resistance exercise

Abstract: . Timing of amino acid-carbohydrate ingestion alters anabolic response of muscle to resistance exercise. Am J Physiol Endocrinol Metab 281: E197-E206, 2001.-The present study was designed to determine whether consumption of an oral essential amino acid-carbohydrate supplement (EAC) before exercise results in a greater anabolic response than supplementation after resistance exercise. Six healthy human subjects participated in two trials in random order, PRE (EAC consumed immediately before exercise), and POST (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
368
5
16

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(418 citation statements)
references
References 29 publications
18
368
5
16
Order By: Relevance
“…Esmarck et al (140) concluded that the intake of a protein supplement immediately after each bout of resistance-type exercise was required for skeletal muscle hypertrophy to occur with a 12-week intervention in the elderly. Although the absence of any hypertrophy in the control group seems to conflict with previous studies that show muscle hypertrophy following resistance training without any dietary intervention, the proposed importance of nutrient timing is supported by more recent studies investigating the impact of AA or protein co-ingestion prior to, during and/or after exercise on the acute muscle protein synthetic response (141,142) . Verdijk et al (117) compared increases in skeletal muscle mass and strength following 3 months of resistance exercise training with or without protein ingestion prior to and immediately after each exercise session in elderly males.…”
Section: Long-term Interventionsmentioning
confidence: 73%
“…Esmarck et al (140) concluded that the intake of a protein supplement immediately after each bout of resistance-type exercise was required for skeletal muscle hypertrophy to occur with a 12-week intervention in the elderly. Although the absence of any hypertrophy in the control group seems to conflict with previous studies that show muscle hypertrophy following resistance training without any dietary intervention, the proposed importance of nutrient timing is supported by more recent studies investigating the impact of AA or protein co-ingestion prior to, during and/or after exercise on the acute muscle protein synthetic response (141,142) . Verdijk et al (117) compared increases in skeletal muscle mass and strength following 3 months of resistance exercise training with or without protein ingestion prior to and immediately after each exercise session in elderly males.…”
Section: Long-term Interventionsmentioning
confidence: 73%
“…Throughout the intervention, each training session was preceded by a 5 minutes general warm-up (cycling or running), followed by two lower body warm-up sets prior to lower body exercises and two upper body warm-up sets prior to upper body exercises, as described in Rønnestad et al (2007). During each warm-up session, each subject ingested a 50g Squeezy Recovery bar (Squeezy AS, Loddefjord, Norway), containing 15g milk protein, ensuring a muscle growth-stimulating nutritional status (Tipton et al 2001). Training intensity, measured as numbers of RMs, was increased similarly in 3U1L and 1L3U, as described in Rønnestad et al (2007): weeks 1-2, 10RM; weeks 3-5, 8RM; weeks 6-12, 7RM.…”
Section: Insert Table 1 Around Herementioning
confidence: 99%
“…Tipton et al (17) , por exemplo, demonstraram apenas que o aumento da síntese proteica após o exercício poderia estar relacionado com o maior do fluxo sanguíneo para a musculatura exercitada, após a sessão de treino. Porém, neste estudo não foi feita nenhuma avaliação ou inferência da participação da síntese endógena NO na resposta de vasodilatação.…”
Section: Discussionunclassified